Measuring. Monitoring. Management. Control - S.V. Logunov; E.V. Blagodyrenko; I.S. Gerasimenko; N.A. Kupriyanov (Измерение, мониторинг, управление, контроль)
Background. The task of preventing orbital incidents requires monitoring the occupancy of the working and intermediate orbits of multi-satellite space systems with high-precision determination of the current navigation parameters of each observed satellite, both taking into account the movement of objects in circular orbits and maneuvering with ion engines turned on. The various types of means used for satellite observation (optical and radar) have complementary characteristics, the generalization of which would allow for daily all-weather measurements of the current navigation parameters of maneuvering satellites and to maintain their catalog with accuracy corresponding to the coordinate spread within tens of centimeters. When summarizing the results of significantly uneven measurements, a contradiction arises between the methods of forming the satellite reference orbit obtained from radar measurements and the necessary condition for the reference orbit to fall into the range of estimates of current navigation parameters during a measurement session with optical means for their joint processing. Materials and methods. To solve this problem, the authors propose the combination and integration of non-precision measurements, which, in turn, requires determining the threshold values of measurement errors. The choice of measurement error thresholds is related to the very concept of significantly uneven measurements of current navigation parameters. It is shown that the threshold at which the transition from combination to integration of non-precision measurements takes place will be determined by the ratio of the values of the COE of various measuring instruments. It is taken into account that the size of the confidence interval at the point of abrupt change in the confidence interval of the estimated current navigation parameters of the satellite from the forecast area is determined by the values of the forecast time interval, and the size of the confidence interval from the measurement area is determined by the instrumental error of the optical means. This made it possible to consider the area of instrumental error of the optical means for each measurement as a new boundary of the confidence interval of a random variable having a distribution with parameters corresponding to the end of the forecast section. Then, using the known provisions of probability theory, the error thresholds were determined. Results. The dependence between the threshold value of the confidence probability and the corresponding value of the guarantee coefficient has been established. The values of the error threshold vectors for estimates of the current navigation parameters of satellites are obtained, which are formed during the transition from one measurement site or forecast to another with known error estimation vectors of the current navigation parameters. This makes it possible to calculate the values of the error threshold vectors for estimating the current navigation parameters of satellites, including maneuvering ones, at any given time. Conclusions. The implementation of the proposed approach will ensure compliance with the requirements for preventing orbital incidents in space in terms of accuracy and efficiency by combining information about the space situation from different types of measuring instruments. It is established that there is a confidence limit for the ratio of errors of quantities during their joint processing, above which the result of aggregation becomes guaranteed unreliable. In the article, the value of this limit is determined for the case of a normal distribution.